In vivo and in vitro characterization of GL0034, a novel long‐acting glucagon‐like peptide‐1 receptor agonist. Issue 11 (18th July 2022) - Jones, Ben; Burade, Vinod; Akalestou, Elina; Manchanda, Yusman; Ramchunder, Zenouska; Carrat, Gaëlle; Nguyen‐Tu, Marie‐Sophie; Marchetti, Piero; Piemonti, Lorenzo; Leclerc, Isabelle; Thennati, Rajamannar; Vilsboll, Tina; et al.
Abstract: Aims: To describe the in vitro characteristics and antidiabetic in vivo efficacy of the novel glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) GL0034. Materials and Methods: Glucagon‐like peptide‐1 receptor (GLP‐1R) kinetic binding parameters, cyclic adenosine monophosphate (cAMP) signalling, endocytosis and recycling were measured using HEK293 and INS‐1832/3 cells expressing human GLP‐1R. Insulin secretion was measured in vitro using INS‐1832/3 cells, mouse islets and human islets. Chronic administration studies to evaluate weight loss and glycaemic effects were performed in db/db and diet‐induced obese mice. Results: Compared to the leading GLP‐1RA semaglutide, GL0034 showed increased binding affinity and potency‐driven bias in favour of cAMP over GLP‐1R endocytosis and β‐arrestin‐2 recruitment. Insulin secretory responses were similar for both ligands. GL0034 (6 nmol/kg) led to at least as much weight loss and lowering of blood glucose as did semaglutide at a higher dose (14 nmol/kg). Conclusions: GL0034 is a G protein‐biased agonist that shows powerful antidiabetic effects in mice, and may serve as a promising new GLP‐1RA for obese patients with type 2 diabetes.